Structure of the wild-type human BCL6 POZ domain - Stead, Mark A. (International Union of Crystallography, 2008)
BCL6 is a transcriptional repressor that is overexpressed in diffuse large B-cell lymphoma and follicular lymphoma. The N-terminal POZ domain of BCL6 interacts with transcriptional corepressors and targeting these associations is a promising therapeutic strategy. Previous structural studies of the BCL6 POZ domain have used a mutant form because of the low solubility of the wild-type recombinant protein. A method for the purification and crystallization of the wild-type BCL6 POZ domain is described and the crystal structure to 2.1 Å resolution is reported. This will be relevant for the design of therapeutics that target BCL6 POZ-domain interaction interfaces.